Investigating the Role and Mechanism of Octreotide in Long Standing Diabetes-induced Cognitive Impairment in Rats - Yuan, Qi; Feng, Jia (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Octreotide is a somatostatin analogue and it produces beneficial effects in diabetic-neuropathy. Studies have also shown its beneficial role in Alzheimer disease. However, the role of octreotide in diabetes-induced cognitive impairment is not explored yet. Aim: The present study was designed to explore the role and mechanism of octreotide in long standing diabetes-induced cognitive impairment in an experimental model. Materials and Methods: Streptozotocin (60 mg/kg)-injected rats were kept for 10 weeks to induce the development of cognitive impairment, which was assessed using Morris Water Maze test. The learning was assessed by comparing the escape latency time (ELT) of day 1 with ELT of day 4. The memory was assessed on the 5th day by measuring the time spent in target quadrant (TSTQ). Three different doses of octreotide (10, 20 and 40 μg/kg) were administered for the last two weeks. The levels of Nrf2, reduced glutathione, TBARS, IL-1 and TNF-α were measured in rat brain homogenates. Results: Treatment with octreotide for two weeks led to significant increase in day 4 ELT and day 5 TSTQ in streptozotocin-injected rats suggesting the improvement in learning and memory. Moreover, octreotide attenuated streptozotocin-induced increase in neuroinflammation and oxidative stress. It also increased the nuclear: cytoplasmic ratio of Nrf2 suggesting the effect of octreotide in increasing the levels of endogenous antioxidants. Conclusion: Octreotide has the potential to improve learning and memory in long standing diabetes-induced cognitive dysfunction and its beneficial effects may be possibly attributed to decrease in neuroinflammation and oxidative stress.
Keywords: Oxidative stress; Diabetes; Memory; Octreotide; Neuroinflammation; Learning